Domestic and Foreign Banks' Stability in Indonesia: The Grey Zone Trap and Key Determinants - Vanessa Purnawan; Ahmad Danu Prasetyo (Research Synergy Foundation, 2021)
The recent global financial crisis in 2008 has comprehensively predisposed the stability of most banking sectors worldwide, but not in Indonesia. As reported by IMF, the Indonesian banking industry showed such a remarkable stability level, facing negative shocks. However, an important question persists: whether Indonesian domestic banking sectors are truly stable or the foreign-owned banks are the ones that give a more significant share of stability contribution. Hence, this paper investigates the stability level using the Z-score modification model and assesses the main constituents that impart the stability levels of foreign and domestic banks by applying VECM of micro-prudential and macroeconomics indicators. The research is based on the aggregate data of Indonesian foreign and domestic banks from the year 2005 to 2015. The result then shows that the grey zone bridled the domestic banking sector in Indonesia, a high alert partial safe zone, due to its incommensurate loan control, inefficiency in generating profitability and liquidity from assets, and lack of capital buffers presence. Nevertheless, the findings also reveal that neither domestic nor foreign banks in Indonesia were completely safe against credit risk.